Legal Study on the Rejection of Land Deed Officials Against Deeds of Sale and Purchase of Land Rights for the Community in Jayapura Regency - Palenewen, James Yoseph; Manengkey, Victor Th. (PT. Riset Press International, 2025)
The rejection of Land Deed Officials against deeds of sale and purchase of land rights for the community in Jayapura Regency still often occurs today. This study aims to determine the application of Article 39 paragraph (1) of Government Regulation Number 24 of 1997 and determine the factors that cause Land Deed Officials to refuse to make deeds of sale and purchase for the community in Jayapura Regency. The method used in this study is normative and empirical juridical, which refers to laws, literature, written regulations, or other secondary legal materials and identifies and conceptualizes law as a fundamental social institution in a real-life system. The results of this study reveal that the implementation of Article 39 paragraph (1) of Government Regulation Number 24 of 1997 concerning Land Registration has been carried out adequately based on applicable laws and regulations, not all candidates who want to make a deed of sale and purchase are accepted by the Land Deed Making Officer because the PPAT checks the truth first, both physically and legally, whether or not the files brought by the parties are correct so as not to violate applicable laws and regulations and prevent disputes from occurring in the future. Meanwhile, the factors that cause PPATs to refuse to make deeds of sale and purchase for the community in Jayapura Regency are still based on the applicable laws and regulations, especially in Article 39 paragraph (1) of Government Regulation Number 24 of 1997 concerning Land Registration, namely, among other things, the parties who wish to carry out a sale and purchase transaction before the PPAT do not submit the original Certificate of land rights or sometimes the Certificate submitted does not match the lists at the Land Office, regarding land plots that have not been registered, they are not given proof of rights as referred to in Article 24 paragraph (1) of PP 24/1997 or a statement from the Village/Sub-district Head stating that the person concerned controls the land plot.